Pediatric Sedation during Imaging-a Short Review - Begum, Fatima; Bhowmick, Dilip Kumar (Bangladesh Journal of Nuclear Medicine, 2018)
Pediatric sedation is growing practices in specialties outside anesthesia such as in emergency departments, dental chambers, gastroenterology department, imaging facilities and ambulatory services. In imaging departments usually sedation is needed to immobilize the ill children and adjust behavior to cooperate. The objectives of this article are to make awareness of different levels of sedation, safety measures, need for adequate and advanced training on emergency airway management or resuscitation of non anesthesiologist physicians and medical personnel responsible for sedation. Presedation evaluation of pediatric patients, sedation drugs, necessary equipments for resuscitation, monitoring during sedation and discharge of patients in safe condition have been discussed. Bangladesh J. Nuclear Med. 19(2): 142-145, July 2016